KEABSAHAN AKTA PENGIKATAN JUAL BELI TERHADAP SERTIPIKAT YANG DIBUAT NOTARIS UNTUK JAMINAN UTANG PIUTANG ORANG PERORANGAN (STUDI PUTUSAN NO. 2564K/PDT/2019 - Balqis Davya Guci, Samira; Purba, Hasim; Sembiring, Rosnidar (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Debt problems often arise due to the failure of loan payments, leading the lender to take steps such as creating a power of attorney and a sale and purchase agreement. This study aims to analyze the validity of sales based on debt and the legal consequences and protection for the owner of the collateral object. The research method used is descriptive qualitative, focusing on legal norms found in legislation and court rulings. The results show that the sale of collateral in Ruling No. 2564K/PDT/2019 was declared void by law because there was no absolute power of attorney. The sale of collateral objects can only be conducted if the debt is accompanied by a debt acknowledgment deed. For personal debt, execution must be preceded by a lawsuit for default in court. The ruling states that the sale and purchase deed, based on the power of attorney to sell, was annulled by the court as it did not comply with the legal provisions concerning collateral in personal debt, rendering the agreement void. This is reinforced by Article 1335 of the Civil Code, which states that an agreement made without a valid cause or based on a false or illegal cause has no legal effect. Legal protection for the owner of the land rights is reflected in the annulment of the sale and purchase deed and power of attorney to sell, thereby automatically returning the Right to Build Certificate (SHGB) to the original owner, with the obligation to repay the debt as required by law.